Quantitative analysis of modeled ATP hydrolysis in water by a colorimetric sensor array. Issue 50 (31st May 2016) - Minami, Tsuyoshi; Emami, Fereshteh; Nishiyabu, Ryuhei; Kubo, Yuji; Anzenbacher, Pavel
Abstract : A self-assembled and colorimetric sensor assay is utilized to monitor a model of a metabolic reaction where ATP is hydrolyzed to pyrophosphate and AMP. Abstract : Self-assembled colorimetric sensors have been prepared from Zn II –DPA-attached phenylboronic acid (1 ·Zn) and catechol-type dyes. The1 ·Zn–dye sensors display selectivity towards oligophosphate over monophosphates. The colorimetric sensor assay (1 ·Zn–dye) is utilized to monitor a model of a metabolic reaction where ATP is hydrolyzed to pyrophosphate (PPi) and AMP.